Resources, environmental change, and survival: asymmetric paths of young independent and subsidiary organizations - Bradley, Steven W.; Aldrich, Howard; Shepherd, Dean A.; Wiklund, Johan (Strategic Management Journal, 2011)
Abstract Using an evolutionary model and a sample of 7,166 firms in the manufacturing and technology sectors of Sweden, we find that surviving organizations founded independent of a parent organization have lower long‐term failure rates than their protected subsidiary counterparts. Specifically, we find that subsidiary organizations have low mortality rates when compared to independent organizations, but that their mortality rates increase more rapidly during a severe economic downturn. We also find evidence that surviving independent organizations are more capable than subsidiary organizations of using their resources to reduce mortality rates during an environmental jolt. Overall, our findings strengthen the notion that organizational adaptation is linked not only to ecological and strategic processes but also to organizational structure. Copyright © 2010 John Wiley & Sons, Ltd.